Development of a targeted metagenomic approach to study a genomic region involved in light harvesting in marine Synechococcus. Issue 2 (24th February 2014) - Humily, Florian; Farrant, Gregory K.; Marie, Dominique; Partensky, Frédéric; Mazard, Sophie; Perennou, Morgan; Labadie, Karine; Aury, Jean‐Marc; Wincker, Patrick; Nicolas Segui, Audrey; Scanlan, David J.; Garczarek, Laurence
Abstract Synechococcus, one of the most abundant cyanobacteria in marine ecosystems, displays a broad pigment diversity. However, the in situ distribution of pigment types remains largely unknown. In this study, we combined flow cytometry cell sorting, whole‐genome amplification, and fosmid library construction to target a genomic region involved in light‐harvesting complex (phycobilisome) biosynthesis and regulation. Synechococcus community composition and relative contamination by heterotrophic bacteria were assessed at each step of the pipeline using terminal restriction fragment length polymorphism targeting the petB and 16S rRNA genes, respectively. This approach allowed us to control biases inherent to each method and select reliable WGA products to construct a fosmid library from a natural sample collected off Roscoff (France). Sequencing of 25 fosmids containing the targeted region led to the assembly of whole or partial phycobilisome regions. Most contigs were assigned to clades I and IV consistent with the known dominance of these clades in temperate coastal waters. However, one of the fosmids contained genes distantly related to their orthologs in reference genomes, suggesting that it belonged to a novel phylogenetic clade. Altogether, this study provides novel insights into Synechococcus community structure and pigment type diversity at a representative coastal station of the English Channel.